Neurological syndromes associated with COVID-19: a multicenter study in Brazil - Aline de Moura Brasil Matos; Andre Borges Ferreira Gomes; Fernanda Martins Maia Carvalho; Francisco Tomaz Meneses de Oliveira; Lohana Santana Almeida da Silva; Flavia Esper Dahy; Joao Victor Luisi de Moura; Marcela Vieira Freire; Jose Ernesto Vidal; Rosa Maria Nascimento Marcusso; Jerusa Smid; Victor Rebelo Procaci; et al. (BMC Infectious Diseases)
Abstract Background Neurological manifestations associated with COVID-19 remain partially described, mainly in low- and middle-income countries where diagnostic tools are limited. To address this, we assembled medical centers in Brazil with the goal of describing neurological syndromes associated with COVID-19 during the first wave of the pandemic. Methods From June 1st, 2020 to June 1st, 2021, non-consecutive adult patients with new onset of six neurological syndromes up to 60 days after confirmed COVID-19 were included. Data were compiled from four tertiary centers and compared with general local COVID-19 data, as well as with a previous cohort focused on vascular syndrome. Results 197 patients were included, presenting with vascular syndromes (81), encephalopathy (68), encephalitis (19), Guillain-Barré syndrome (13), other neuropathies (12), and myelitis (4). The incidence curve of neurocovid mirrored that of COVID-19. Neurological syndromes were present regardless of COVID-19 severity. The median time from COVID-19 to onset of neurological symptoms was 14 days, suggesting a post-infectious immune-mediated mechanism. Patients were 10 times more likely to die (χ2 (1) = 356.55, p < 0.01, OR = 10.89) and 38 times more likely to be hospitalized than other COVID-19 patients (χ2 (1) = 1167.9, p < 0.01, OR = 38.22). Those developing vascular syndromes patients were 3 times more likely to require ICU (χ2 (1) = 37.12, p < 0.01, OR = 3.78) and 4 times more likely to die (χ2 (1) = 58.808, p < 0.01, OR = 4.73) than patients with vascular syndromes due to different etiologies. Conclusions Our study corroborates the association of neurological syndromes with COVID-19. The incidence correlated with local waves of COVID-19, and patients with neurocovid exhibited a higher susceptibility to adverse outcomes compared to other COVID-19 patients. Among all neurological syndromes, vascular syndromes were the most common, and their severity surpassed that of vascular syndromes not attributed to COVID-19.